(untitled) (Південний архів (історичні науки), 2022)
The study analyzes changes in the definition of “information war” in the works of Ukrainian and foreign researchers and the genesis of this concept. Namely, why Western authors were mostly interested in technical and cybernetic aspects of the concept (considering information in the mathematical field), while Ukrainian authors, especially historians and political scientists, have shown interest in historical and psychological (information in the context of propaganda). The purpose of the study is to analyze differences between the “historical-psychological” and “technological-cybernetic” understanding of the concept of “information warfare” (and its variations) in Ukrainian and foreign literature, examining the chronology, causes and consequences of these differences. Research methods are based on comparative analysis, comparing phenomena vertically (chronological changes in the interpretation of information warfare) and horizontally (regional differences). Having determined the chronology of how the concept is read in Ukraine, we identify the genesis of the concept and the time of differences in defining it between the regions of the world. The results of the study: 1) the interpretations of “information warfare” in both Europe and North America have their origins in the works of Canadian culturologist M. McLuhan in the 1960s, however, various conclusions were made in different regions from his works on the medium; 2) historical and psychological aspects were present in American thought even before the 2010s, but lost in the “struggle for recognition” (and funding) to the technological-cybernetic paradigm in the 1990s; 3) the historical development of the first decades of the 21st century has shown the United States the need to pay attention to psychological operations among all aspects of information operations again; 4) the concept of “information war” present in Ukrainian works is not an ideal translation of the English “information warfare”, as the term is about information methods of waging war, not of an “information war” in itself.